Survey of changes in subjective symptoms among Japanese polio survivors over 10 years - Fumi Toda; Koshiro Sawada; Daisuke Imoto; Kazuya Hayashi; Shun Fujii; Eiichi Saitoh; Yohei Otaka (Journal of Rehabilitation Medicine)
Objective: To define long-term changes in subjective symptoms among polio survivors in Japan.